Development and validation of the Eyewitness Metamemory Scale. Issue 5 (22nd July 2019) - Saraiva, Renan Benigno; van Boeijen, Inger Mathilde; Hope, Lorraine; Horselenberg, Robert; Sauerland, Melanie; van Koppen, Peter J.
Summary: Metamemory can be defined as the knowledge about one's memory capabilities and about strategies that can aid memory. In this paper, we describe the development and validation of the Eyewitness Metamemory Scale (EMS), tailored specifically for use in face memory and eyewitness identification settings. Participants ( N = 800) completed the EMS and other measures on general metamemory. Results from exploratory and confirmatory factor analysis revealed good factorial validity, internal consistency, and content validity. The EMS items emerged into three distinct factors: memory contentment, memory discontentment, and memory strategies. The EMS is a brief and easily administrable questionnaire that might be used to assess self‐ratings of face recognition capacity and use of strategies to encode faces.